The Methods to Overcome ATP-binding Cassette Transporters-mediated Multi-drug Resistance - Mansoureh Entezar-e-Ghaem; Soheila Rahgozar; Ali Reza Moafi (مجله دانشکده پزشکی اصفهان, 2013)
Background: Multi-drug resistance (MDR) is a prevalent phenomenon occurred in tumor cells in response to chemotherapy. The main cause of MDR is the efflux of drugs by ATP-binding Cassette (ABC) transporters. Since identifying the role of these proteins in resistance to chemotherapeutic agents, extensive researches have been started to find out methods to selectively overcome their effects. The purpose of this study was to review the methods used to conquer ABC transporters-mediated MDR. Methods: Reviewing more than 70 basic and recently published articles, this paper is discussing the methods of defeating MDR. Findings: The first step to counteract the ABC transporters effects is using chemical inhibitors. Unpredictable cytotoxicity and side effects of these modulators may require more attentiveness in their clinical application. Another technique in this regard is the use of drug delivery systems such as nanoparticles and liposomes. This method can be employed along with sonication to improve the specificity. Down-regulation of ABC transporters expression by means of RNA interference system is another method to overcome MDR. siRNA and shRNA are utilized in this system and are introduced into the cells by various carriers such as viral vectors, lipid carriers and chemical polymers. Destruction of mRNA is the aim of this method. Conclusion: Despite great advances in overcoming ABC transporters-mediated MDR, most of the techniques are in preclinical and early stages of clinical trials and await more delineation for becoming clinically applicable. Two main reasons for this slow progress are wide range of substrate specificity as well as the tissue distribution of ABC transporters. Keywords: Multiple drug resistance, ATP-binding cassette transporters, Membrane transport modulators, Drug delivery systems, RNA interference